UTILIZATION OF TERRESTRIAL LASER SCANNING AND HANDHELD SCANNER METHODS IN TERRESTRIAL 3 DIMENSIONAL MAPPING FOR DEVELOPMENT OF UTILITY MANAGEMENTCASE STUDY: PUSAT ANTAR UNIVESITAS BUILDING (PAU) - Ariq Naufal, Muhammad
Terrestrial Laser Scanning (TLS) and Handheld Scanner (HS) are methods used in the 3-dimensional terrestris mapping (3D), using scanning technology with Laser beams. The TLS and HS methods can result in millions of points (point clouds) with the precision of achieving a millimeter order. The application of this method can be used to construct a utility management on a multilevel building. Utility management is the process of management, maintenance, and maintenance of the utility object, to support utilities to function properly. In building a utility management, TLS and HS methods can be utilized to generate utility path visualizations from 3D model utilities, which are useful in the process of object maintenance. The 3D models are created using TLS and HS clouds with scan to BIM and parametric modelling methods. A semantic attribute added to a 3D model utility will build a database of utilities required by the building manager, especially the manager of the Pusat Antar Universitas (PAU) Building. Analysis carried out is the analysis of data point TLS and HS clouds in the manufacture of 3D models. Analysis of the data point of TLS and HS clouds is done by comparing the level of object visualization details from the TLS and HS clouds point. The results of the research obtained is the use of HS clouds data point with a density of 1-4 mm can help the data point TLS with a density of 12.5 mm to visualize the utility object in more detail. However, the location of the utility object which is generally located at the ceiling of the building, making the size of the utility object can not be visualized properly by the data point of the TLS or HS clouds. To obtain object size information, a collection of information is performed through an analog document utility object that is managed by a building utility Manager. Thus, objects of a size that cannot be visualized properly can be modeled using a parametric modelling method, using the size of an object that has been obtained from an analog document.